Self-protection in Greece: sticking with groups, communicating, protesting, and fighting. Issue 4 (19th May 2018) - Karas, Tania; Bock, Joseph G.
ABSTRACT: Despite the international community's responsibility to protect (R2P) mandate, we are years away from effective international enforcement mechanisms. It is therefore important that we better understand and seek to support local capacities for self-protection. Migrants and refugees in Greece have shown us four central ways they cope with insecure environments. They stick together in groups, communicate warnings of danger, protest when conditions are threatening, and fight when all else fails. This practical note offers three recommendations on how to support the capacity of displaced people to protect themselves.